1994×1994-1993×1993 用简便算法
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 18:40:11
1994×1994-1993×1993用简便算法1994×1994-1993×1993用简便算法1994×1994-1993×1993用简便算法原式=(1994+1993)*(1994-1993)=3
1994×1994-1993×1993 用简便算法
1994×1994-1993×1993 用简便算法
1994×1994-1993×1993 用简便算法
原式=(1994+1993)*(1994-1993)=3987*1=3987
=(1994+1993)(1994-1993)=3987
1994×1994-1993×1993
=(1994+1993)*(1994-1993)
=3987
1994×1994-1993×1993
=1994²-1993²
=(1994+1993)×(1994-1993)
=3987
1994*1994-1995*1993
1994×1994-1993×1993 用简便算法
1993+1992*1994分之1993*1994-1
1993×1994-1分之1993+1992×1994
计算:1993+1994*1992/1993*1994-1
多位数数学题1993×19941994-1994×1993
1993除以1993又1994分之1993
1994*19931994-1993*19941994
1994*19931994-1993*19941994
1992/1993+1993/1994+1994/1995=?1992/1993+1993/1994+1994/1995=?
19931994*1994-19931994*1993
巧算1993 +1994*1992/1993*1995-1994急.1993 +1994*1992/1993*1995-1994过程
(1992/1993+1993/1994+1/2)*(1992/1993+1993/1994+1994/1995)-(1992/1993+1993/1994+1994/1995+1/2)*(1992/1993+1993/1994)
(1993+1992×1994)÷(1993×1994-1)我需要简便算法,
1995*1995+1994*1994-1995*1994-1994*1993
(1994+1995*1993)/(1994*1995-1)
1995又1/1993×1993/1994
简便计算:1993*1994-1分之1993+1992*1994